Climate-Smart Agriculture Investment Plan Development Guide: From Concept to Action - World Bank; Adaptation of African Agriculture; International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security; World Agroforestry Centre (2019)
The Paris Agreement defined at the United Nations Framework Convention on Climate Change (UNFCCC) 21nd Conference of Parties (COP21, 2015) in France, unified the global community toward the common cause of adapting to climate change, reducing greenhouse gas emissions and fostering sustainable development. The climate challenge to agriculture in Africa was recognized the following year at COP22 (2016) in Marrakech, Morocco, where the Moroccan government launched the Adaptation of African Agriculture (AAA) Initiative. This initiative aimed to highlight the investment needs for helping African countries cope with climate change risks to agriculture and best position themselves for a future of higher temperatures, uncertain precipitation and increased frequency of extreme events. The AAA Initiative builds on the Comprehensive African Agriculture Development Programme (CAADP), first launched in 2003 through the African Union, which promotes the development of national agricultural investment plans (NAIPs) for African countries. The development of climate-smart agriculture investment plans (CSAIPs) has been identified as important for identifying priority CSA projects and making the case for funding and financing.